Genes VII - Lewin, Benjamin (Oxford University Press, 2000)
"Genes VII, the latest edition of this textbook, covers the material that is at the heart of current courses in molecular biology, genetics, cell biology, and related disciplines. In a change to the approach of all previous editions, which started with a traditional analysis of formal genetics, the seventh edition presents the subject in the context of the eukaryotic gene as revealed in the last decade, an analysis based directly on the molecular properties of the gene itself. The new approach has made the book more concise and a new design presents the material in a refreshingly clear manner." "Genes VII gives an integrated account of the structure and function of genes in both prokaryotic and eukaryotic organisms."--Jacket.